THE EXTRACTION OF OIL FROM Nannochloropsis sp. MICROALGAE USING ULTRASONIC AND FERMENTATION AS CELL DISRUPTION - Dhiti Adiya Hanupurti; Onie Kristiawan (Scientific Contributions Oil and Gas, 2014)
Algae are a promising source of biofuel but claims about their lipid content can be ambiguous becauseextraction methods vary and lipid quantitation often does not distinguish between particular lipid classes.One of algae types that meet this condition is Nannochloropsis sp. Two different cell disruption methods,i.eultrasonic and fermentation followed by maceration extraction using a mixture of ethanol/hexane (1:1, v/v)as a solvent extraction were studied for their effectiveness in extraction of algae lipids from Nannochloropsissp. Contact time and amplitude were varied in ultrasonic process. Hydrolysis treatment was varied infermentation process, i.e Dillute Acid Pretreatment (DAP) hydrolysis, enzymatic hydrolysis and DAP withenzymatic hydrolysis. The result showed that ultrasonic process followed by maceration extraction wasmore effective for Nannochloropsis sp. lipid extraction. The most ideal treatment was at amplitude 40%and contact time 5 minutes with lipid content of 63.59% of dry weight.